Separation and Analysis of Boron Isotope in High Plant by Thermal Ionization Mass Spectrometry - Qingcai Xu; Yuliang Dong; Huayu Zhu; Aide Sun (International Journal of Analytical Chemistry, 2015)
Knowledge of boron and its isotope in plants is useful to better understand the transposition and translocation of boron within plant, the geochemical behavior in the interface between soil and plant, and the biogeochemical cycle of boron. It is critical to develop a useful method to separate boron from the plant for the geochemical application of boron and its isotope. A method was developed for the extraction of boron in plant sample, whose isotope was determined by thermal ionization mass spectrometry. The results indicated that this method of dry ashing coupled with two-step ion-exchange chromatography is powerful for the separation of boron in plant sample with large amounts of organic matters completely. The ratios of boron isotope composition in those plant tissue samples ranged from -19.45‰ to +28.13‰ (total range: 47.58‰) with a mean value of 2.61±11.76‰ SD. The stem and root isotopic compositions were lower than those in flower and leaf. The molecular mechanism of boron isotope may be responsible for the observed variation of boron isotopic composition and are considered as a useful tool for the better understanding of boron cycling process in the environment and for the signature of living systems.